The impact of perceived value and affection on Chinese residents' continuous use intention of mobile health science information: An empirical study - Kun Tian; Kun Tian; Lijie Hao; Lijie Hao; Wenxia Xuan; Wenxia Xuan; Thanawan Phongsatha; Ruimin Hao; Wenjing Wei (Frontiers Media S.A., 2023)
IntroductionDisseminating health science information via the internet has become an essential means for improving Chinese residents' health literacy, which has received constant attention from the Chinese government. Therefore, it is important to explore Chinese residents' perceived value and emotional response to mobile health science information for determining Chinese residents' satisfaction and use intention.MethodsThis study applied the cognition-affect-conation model to evaluate the perceived value, arousal, pleasure, trust, satisfaction, and continuous use intention. A mobile device was used to obtain health science information from 236 Chinese residents via an online survey and the data were analyzed using partial least squares (PLS)-structural equation modeling.ResultsThe results showed that Chinese residents' perceived value of health science information obtained using the mobile device directly affect the degree of arousal (β = 0.412, P < 0.001), pleasure (β = 0.215, P < 0.01), and trust (β = 0.339, P < 0.001). The degree of arousal (β = 0.121, P < 0.01), pleasure (β = 0.188, P < 0.01), and trust (β = 0.619, P < 0.001) directly affected Chinese residents' satisfaction, which further affected their continuous use intention (β = 0.513, P < 0.001). Similarly, trust directly affected Chinese residents' continuous use intention (β = 0.323, P < 0.001). The degree of arousal directly affected their degree of pleasure (β = 0.304, P < 0.001), and pleasure also imposed a direct effect on trust (β = 0.293, P < 0.001).DiscussionThe result of this study provided an academic and practical reference to improve mobile health science popularization information. Affective changes have imposed an important effect on Chinese residents' continuous use intention. High-quality, diversified and frequent use of health science information can significantly increase residents' continuous use intention, improving their health literacy as a consequence.